An Investigation into Online Shopping Cart Abandonment in South Africa - Benson, Lesley G.; Ndoro, Tinashe TR (International Review of Management and Marketing, 2022)
The research sought to investigate the factors that impact consumers’ online shopping cart abandonment in South Africa. The factors that impact online shopping cart abandonment which were under investigation included perceived security risks, perceived costs and organisation and research. A quantitative research design was adopted in the study and data was collected from respondents. The respondents consisted of consumers who are over the age of 18 and reside in South Africa. Structural equation modelling was used to analyse the data. The resulted showed that perceived security risks, perceived costs and organisation and research have a statistically significant impact on online shopping cart abandonment. The findings of this study offer businesses insight into the consumer motivations for abandoning their online shopping carts. This area of research has not been fully explored in developing countries, including South Africa.